Percampuran Kod Dalam Media Sosial - Irvine Pong, Ronnie Ugat (Universiti Malaysia Sarawak (UNIMAS), 2024)
This study aims to examine the use of code-mixing in communication on social media. There are three objectives in this study: to identify the types of code-mixing that occur on social media, to identify the word classes with the highest frequency in the code-mixing data, and to identify the functions of code-mixing usage in the context of utterances. This is a descriptive qualitative study that investigates code-mixing on social media. The data for this study were obtained from the social media accounts @astrogempak and @ohbulanofficial. In this study, the researcher employed observational analysis by collecting data from those accounts, as well as content analysis. For data analysis, the researcher analyzed the data using three different theories based on the study objectives. Based on the first objective, all three types of code-mixing were found in this study. However, the Insertion type occurred most frequently, followed by Alternation and Congruent Lexicalization. Next, the researcher examined the most frequent word classes found in the data: nouns (18), verbs (16), adjectives (3), and function words (0). As for the third objective, it was found that representative utterances were the most dominant speech act type based on Searle’s Speech Act Theory (1969). Through these objectives—which include identifying the types of code-mixing, the most frequently used word classes, and the functions of code-mixing in utterances—this study enhances the understanding of bilingual dynamics in modern communication and helps address the lack of documentation on how language is used on social media by Malaysian users